Allu tells stories the following day - Pavel Allu; Valentina Dedyk (Alexander King, 2013)
Allu tells more stories. He is very hard of hearing. The recording is interrupted when he coughs and needs to go spit in the sink. Ambient audio recording of conversation between Allu and Valya as King (depositor) puts away gear. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra.